Enhancing Patient Procedures through Process Improvement: A Systematic Review of Patient-Centered Care Approaches - Al Yami, Hassan Salim Al Sinan; Al Mahamedh, Hadi Hamad Ali; Aljubaily , Jassem Mohammed Ahmed; Alkhaiwani, Ali Hussain; Alfenais, Yasamiyan Ali Bin Yahya; Alnazr, Taha Hussain Abdulaziz; Bukhamseen, Ahmed Abdulaziz Mohammed; Alherz , Haider Shokri Mohammed; Almutlaq, Saud Mohammed Awadh; H, Alqahtani, Faris Almia (Journal of Ecohumanism, 2024)
Patient-centered care is increasingly recognized as a fundamental component of high-quality healthcare, emphasizing the need for healthcare systems to optimize patient procedures. This systematic review explores the role of process improvement methodologies in enhancing patient procedures while aligning with patient-centered care approaches. A comprehensive search of studies published between 2016 and 2023 was conducted across multiple databases, focusing on healthcare interventions using Lean, Six Sigma, and Total Quality Management methodologies. The findings demonstrate that process improvement techniques significantly reduce waiting times, procedural errors, and inefficiencies, ultimately improving patient satisfaction and safety. Moreover, integrating patient-centered care approaches ensures that patients’ needs, preferences, and values are central to healthcare decision-making, further enhancing procedural effectiveness. However, challenges such as resistance to change and resource limitations were noted. This review underscores the importance of combining process optimization with patient-centered care to achieve sustainable improvements in patient outcomes and procedural efficiency. Future research should focus on the long-term impact of these methodologies and the role of technology in further advancing patient-centered approaches.